PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP REPURCHASE INTENTION PADA E-COMMERCE LAZADA (Studi Kasus Pada Pengguna Lazada di Kota Bekasi Tahun 2024) - Nurhayatun, Nunik; Agoestyowati, Redjeki (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to find out how much influence E-Service Quality and E-Trust have on Repurchase Intention in Lazada E-Commerce (Case Study of Lazada Users in Bekasi City 2024). This study uses a quantitative approach. Respondents in this research were consumers who had shopped online at Lazada e-commerce in Bekasi City. The number of respondents used in this research was 150 people. The sampling technique used was a purposive sampling technique with data collection techniques using questionnaires distributed via google forms. Data analysis uses multiple linear regression analysis techniques. The results of this research showed that E-Service Quality (X1) partially has a positive and significant effect on Repurchase Intention (Y) in Lazada e-commerce by 45.4%. Partially, E-Trust (X2) has a positive and significant effect on Repurchase Intention (Y) on Lazada e-commerce by 31.4%. Together E- Service Quality (X1) and E-Trust (X2) have a positive and significant effect on Repurchase Intention (Y) in Lazada e-commerce by 50.9% and the remaining 49.1% is influenced by other variables that were not examined in this research.